Nano-mechanical experiments and analysis of high entropy alloys and single-crystal materials - Jose, Jerin (Nanyang Technological University, 2022)
In recent years, Hight Entropy Alloys (HEA) are becoming ever so popular due to their exceptional mechanical properties, and therefore can be applied for wide applications throughout the industries. The HEA of interest in this paper is HfNbTiZr. The application High- Pressure Torsion (HPT) reduces grain sizes to below 1μm. This significant grain size reductions by means of HPT will increase its strength and some other mechanical properties. The study of this paper consists of producing nanoindentations on an annealed sample, HPT ¼ sample and a HPT5 sample. Firstly, an operational manual for setup, nanoindentation tests in both room temperature and high temperature were established. This manual can be used as a general reference to any tests as it is not specific to any tests. Additionally, post-processing of the data obtained and exported are shown as well. Secondly, based on the manual created, room temperature and high temperature tests are conducted. The results obtained from the tests are processed and analyzed to study the hardness values across varying temperatures and loading rates. The results are studied in conjunction with the grain structures of the samples It was rather noticeable that the grain size has a significant effect on the hardness of the material tested. An improvement in plasticity is also observed by an increase in strain rate sensitivity in the HPT-processed HEAs. The overall hardness values increased as the number of HPT turns are introduced onto the sample as well. However, oxide formation would lead to deviation from the expected results as it causes the hardness values to increase.